Analysis of the Donggala-Palu Tsunami Characteristics based on Rupture Duration (Tdur) and Active Fault Orientation using the HC-plot Method - Ramadhan Priadi; Angga Wijaya; Maria Annaluna Pasaribu; Riska Yulinda (Jurnal Geofisika, 2019)
September 28th, 2018, Donggala-Palu earthquake M 7.5 occurred at depth of 12 km and generated tsunami to be released off the coast in Palu Bay. The tsunami that occurred in Palu was very interesting because the results of the earthquake source mechanism Palu had a type of strike-slip fault that should not have generated a tsunami. This study purpose to estimate the characteristics of the Donggala-Palu tsunami based on rupture duration ( and orientation fault activated using the HC-plot method. The data used in this study are data waveforms from 17 seismic stations and CMT Global catalog data with the area of research 0.87 0 N-1.78 0S dan 118.640E- 120.95 0E. The waveform data used is a phase P-PP vertical component signal with a Bandpass-filter 1-5 Hz for determination . The fastest rupture duration from the earthquake source is obtained from the calculation of each station. Delay time measurement after P wave for 90% (T0.9), 80% (T0.8), 50% (T0.5), dan 20% (T0.2) from its peak value. Then the HC-plot method is used to estimate the orientation of generator fault Palu earthquake and the direction of rupture from the focal mechanism. From the results of processing obtained 2 pairs of seismic stations with almost the same distance but with different azimuths. The fastest rupture duration is at BBSI station with value of 82.014 s and distance from station to epicenter . So that the rupture direction is in the azimuth from the north. The result of fault orientation was obtained hypocenter distance to the centroid for nodal plane 1 is 6.32 km and nodal plane 2 is 30.17 km with distance centroid to hypocenter is 31.22 km. So in Palu earthquake, the tsunami generator fault was in nodal plane 1 with direction north-south. Criteria obtained indicate that the Palu earthquake M 7.5 has potential for a tsunami because of its value has meet ≥ 65 s, but from the result of the focal mechanism direction field not passing through the Palu bay is thought to be another parameter that generates a tsunami and Palu koro fault line uncharted.